Efficiency factors and ecosystem framework in Malaysian Halal Food Certification System / Nurulhuda Noordin - Noordin, Nurulhuda (Institute of Graduate Studies, UiTM, 2014)
The halal market has grown tremendously due to the Muslims’ global demand of halal quality on products as prescribed by the shariah law. Halal is accepted as a quality standard and is applied to product supply and manufacturing encompassing processed food, cosmetics, pharmaceutical and medical products. Halal suppliers or manufacturers must abide to the halal quality regulation enforced by the public, semipublic and private regulatory bodies offering halal certification. These regulatory bodies play an important role within the halal supply chain as their operational efficiency may effect the efficiency and the competitiveness of the halal industry. This research is conducted to investigate the strategic approach on halal quality management to address operational efficiency of the halal food certification system using the Malaysian halal certification as a case study.